Efficacy of the REACH Forgiveness Intervention in Indian College Students - Toussaint, Loren; Worthington, Everett L.; Cheadle, Alyssa; Marigoudar, Savitri; Kamble, Shanmukh; Büssing, Arndt (Frontiers in Psychology, 2020)
The present study investigated the efficacy of the REACH Forgiveness psychoeducation program for the first time in India and examined theoretically-based predictors of program response based on the model of relational spirituality and forgiveness. This was an intervention experiment that spanned five weeks and included three measurement occasions (weeks 1, 3, 5) and two separate deliveries of the forgiveness intervention (weeks 2 and 4). Participants were N = 124 students at Karnatak University in Darwha, India (100 Hindu; 18 Muslim, 5 Christian, and 1 Jain). This was a manualized, secular intervention led by a trained facilitator in a group, psychoeducational format. Measures included forgiveness and unforgiveness as well as assessments of positive and negative affective states and spirituality. Participants who received immediate forgiveness training showed significant and large positive changes in forgiveness and unforgiveness, as well as, more positive affect and increased self-esteem in contrast to wait-list comparisons. Perceiving one’s offender as having a similar spirituality to oneself was a consistent predictor of response to the REACH Forgiveness program. Specifically, perceiving the offender as having a similar spirituality was related to less growth of unforgiveness and more growth in empathy, positive affect, and emotional forgiveness as a result of the psychoeducational program. The REACH Forgiveness psychoeducational approach is efficacious in an Indian student sample, and some relational spirituality variables are important predictors of response to the program. Future studies should consider the role of Indian culture in promoting forgiveness and possibly tailor the intervention to suit the significant proportions of Hindus and Muslims in India.